Direct taxes and income inequaliy: an analysis of China experiences - Lin, Nie; Palil, Mohd Rizal; Turmin, Siti Zaidah (Human Resources Management Academic Research Society (HRMARS), 2024)
This paper examines the impact of direct taxes on income inequality, focusing on how the proportion of direct taxes in total tax revenue affects the Gini coefficient. The core issue of income inequality in China stems from the tax structure and social security system's inadequacies, which place a heavier burden on low-income groups and hinder effective wealth redistribution. The study's primary objective is to explore the relationship between tax structure and income inequality, and to assess whether economic growth, education investment, and the social security system can alleviate this issue. Using quantitative analysis, the study analyzes data from 2013 to 2023 on China's Gini coefficient and direct tax proportion. A fixed effects model controls for variable heterogeneity, and regression analysis confirms that increasing the proportion of direct taxes significantly reduces income inequality. This research is significant as it provides new insights into the role of tax policies in reducing income inequality, particularly in China, a major developing country. The findings offer empirical support for policymakers to design fairer and more effective tax systems. Future research should consider longer timeframes and other factors such as technological advancements, globalization, and demographic changes to better understand the complex relationship between tax policies and income inequality.